Pirate Gear: cannons, swords, and the Jolly Roger - O'Donnell, Liam. (Mankato, MN Capstone Press, 2007)
Presents the tools and equipment pirates used for daily life at sea, as well as the weapons used for their deadly raids on merchant ships
Elementary
Keywords: Pirates